2002
DOI: 10.1103/physrevlett.88.186102
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Interaction of Surface Steps: Effect of Atomic-Scale Roughness

Abstract: Elastic interactions of atomic steps can greatly impact surface morphology. Recent atomistic calculations and experimental observations find the standard dipole model of steps is valid only for very large step separations. In this Letter, a new model is presented that displays remarkable agreement with atomistic predictions for step separations larger than just a few step heights. It is shown that the interaction energy of steps exhibits a novel intermediate-ranged behavior and that, for particular systems, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The effect of such steps on the growth process, the morphology, the stress and strain distributions, and the functionality of the materials has been extensively investigated. [1][2][3][4][5][6][7][8][9][10][11] In particular, these steps are thought to constitute a heterogeneous source of nucleation for the formation of nano-objects and structural defects at the initial stages of the growth of many semiconductor nanostructures. 12,13 It is critically important to identify the nucleation sources for individual nano-objects such as quantum dots and wires because they constitute the fundamental blocks of future nanoelectronics and nanophotonics devices.…”
mentioning
confidence: 99%
“…The effect of such steps on the growth process, the morphology, the stress and strain distributions, and the functionality of the materials has been extensively investigated. [1][2][3][4][5][6][7][8][9][10][11] In particular, these steps are thought to constitute a heterogeneous source of nucleation for the formation of nano-objects and structural defects at the initial stages of the growth of many semiconductor nanostructures. 12,13 It is critically important to identify the nucleation sources for individual nano-objects such as quantum dots and wires because they constitute the fundamental blocks of future nanoelectronics and nanophotonics devices.…”
mentioning
confidence: 99%
“…The nature of the elastic force dipole interaction implies that steps of the same sign (i.e., steps either descending or ascending) exert repulsive forces on each other. The situation is different, and more delicate, with steps of opposite sign [6].…”
Section: Force Dipole Step Interaction: a Reviewmentioning
confidence: 99%
“…Accordingly, these authors were able to make predictions in close agreement with observed relaxations of atomistic simulations. 6 Recall that the interaction energy of two electric dipoles with moments p A and p B at distance r AB is [31] …”
Section: Force Dipole Step Interaction: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important assumption is that we neglect the effect of stress caused by the lattice mismatch between the supported crystal and the substrate, 21 considering this to be sufficiently small. In the straight-step model ͓Fig.…”
Section: Step Equations Of Motionmentioning
confidence: 99%